(untitled) (Economics and region, 2020)
It is quite possible to achieve a decent level of satisfaction of the vital interests of the population provided that the national industry develops at the proper level. This is confirmed by the experience of the G7 countries (USA, UK, Canada, Germany, France, Italy, Japan), demonstrating a high level and quality of life. However, the percentage of industry in Ukraine’s GDP during the years 2006-2015 markedly decreased. The index of satisfying the vital interests of the population by various methods is calculated. It has been established that for all alternative ways, the result of the indicated index follows a trend of gradual decline. Substantially close correlation of the levels of industrial development and satisfaction of the vital interests of the population of Ukraine. The conclusion is made about the urgent need for the development of national industry as the basis for the future existence of Ukrainian man, society, and the state. This should be organically implemented in the format of the tasks of Ukraine in the context of the deployment of global megatrends and sustainable development goals.